Relationship between Adolescents' Knowledge About Casual Sexual Behavior - Murliana (Benih : Journal of Midwifery, 2022)
Adolescence signifies a pivotal transition from childhood to adulthood, marked by various explorations, including sexual behavior. The prevalence of casual sexual behavior among teenagers has raised concerns, influenced by numerous factors, notably the quality of parent-teenager relationships. However, a significant knowledge gap persists among adolescents regarding the meaning and consequences of free sexual behavior. This study aimed to explore the relationship between teenagers' knowledge concerning the impact of promiscuous sexual behavior in SMA Negeri 1 South Payabungan, Class XI IPS. Using an analytical survey method with a cross-sectional approach, the study involved 32 participants. Data were collected through a questionnaire to assess teenagers' knowledge levels. Analysis revealed that the majority of respondents exhibited good knowledge (65.6%), with a minority demonstrating sufficient (15.6%) or insufficient knowledge (18.8%). Furthermore, statistical analysis unveiled correlations between knowledge levels and certain demographic factors, such as age (p value = 0.572), environment (p value = 0.597), and information sources (p value = 0.000). These findings underscore the importance of addressing knowledge gaps and enhancing awareness among teenagers regarding the repercussions of casual sexual behavior. In conclusion, the study highlights the need for targeted interventions and educational initiatives to empower teenagers with comprehensive knowledge and promote responsible sexual behavior in SMA Negeri 1 South Payabungan, ultimately contributing to healthier adolescent development.